Howlet’s Multiple Streams Theory and Policy Innovation: A Case Study of Digital Transformation in Indonesian Governance Post-Presidential Transition - Yusuf, Khanan (Jurnal Ilmu Administrasi Negara (JUAN), 2024)
Leadership transitions often present significant opportunities for policy innovation, especially in governance. This article explores the digital transformation within Indonesia's government following the presidential transition, using Howlett's Multiple Streams Theory as a framework. The theory, which examines the interaction of three streams—problems, policies, and politics—helps to understand how policy agendas are shaped and how windows of opportunity arise. The case study delves into how policy actors leverage these windows during governmental transitions to advance digital reforms. The research highlights the pivotal role of policy entrepreneurs and the combination of internal and external factors that influence policy decisions. Through a qualitative case study method, including in-depth interviews, document analysis, and participatory observations, the study reveals that the transition created a favorable political environment, which enhanced the adoption of digital policies. The findings indicate that the main challenges to digital reform include inter-agency coordination and infrastructure readiness, while the main opportunity lies in the strong political backing for digitalization. This paper concludes by emphasizing the critical role of policy entrepreneurs in aligning the three streams to ensure the success of digital transformation policies. The results offer valuable insights into how political changes can drive innovation in public policy, particularly in the context of digital governance.